2019
DOI: 10.15252/emmm.201910849
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial deoxyguanosine kinase is required for cancer cell stemness in lung adenocarcinoma

Abstract: The mitochondrial deoxynucleotide triphosphate (dNTP) is maintained by the mitochondrial deoxynucleoside salvage pathway and dedicated for the mtDNA homeostasis, and the mitochondrial deoxyguanosine kinase (DGUOK) is a rate‐limiting enzyme in this pathway. Here, we investigated the role of the DGUOK in the self‐renewal of lung cancer stem‐like cells (CSC). Our data support that DGUOK overexpression strongly correlates with cancer progression and patient survival. The depletion of DGUOK robustly inhibited lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 60 publications
5
37
0
2
Order By: Relevance
“…We have previously shown frequent overexpression of DGUOK in lung adenocarcinoma and close association of elevated expression of DGUOK with tumor progression and patient survival (4). Knockout of the DGUOK in H1650 cells significantly inhibited cell migration and invasion ( Figures 5A-D).…”
Section: Nmnat2 Is Upregulated and Correlates With Overall Survival Imentioning
confidence: 78%
See 2 more Smart Citations
“…We have previously shown frequent overexpression of DGUOK in lung adenocarcinoma and close association of elevated expression of DGUOK with tumor progression and patient survival (4). Knockout of the DGUOK in H1650 cells significantly inhibited cell migration and invasion ( Figures 5A-D).…”
Section: Nmnat2 Is Upregulated and Correlates With Overall Survival Imentioning
confidence: 78%
“…We have recently reported that DGUOK overexpression promotes lung adenocarcinoma progression (4). Loss of DGUOK significantly induced mtDNA deletion and inhibited mitochondria complex I activity.…”
Section: Results Dguok Regulates Nad + Biogenesismentioning
confidence: 97%
See 1 more Smart Citation
“…12 CSCs are resistant to conventional chemotherapy and radiation therapy, and can remain dormant for many years before cancer initiation, metastases and relapses. 13 Some previous studies showed that the critical role of CSCs in initiation and development of lung cancer, liver cancer, breast cancer, head and neck squamous cell carcinomas, pancreatic cancer and glioblastoma. [14][15][16][17][18][19] Lung CSCs are considered as the cancer initiating and maintaining cells of lung cancer.…”
Section: Cancer Stem Cells Play a Key Role In Tumorigenesis And Develmentioning
confidence: 99%
“…15 Lin et al reported that lung CSCs are responsible for lung cancer initiation and local or metastatic recurrence, the mitochondrial deoxyguanosine kinase is required for CSCs stemness in lung adenocarcinoma. 13 Wang et al investigated that arsenic and BaP co-exposure produce CSC-like cells and promote the occurrence of lung cancer. 20 Hsu et al reported that lung CSCs confer tumorigenesis and resistance to standard treatment in lung cancer, targeting the upregulated glycolysis and its associated downstream pathways may be the novel strategies for eliminating CSCs and the better prognosis of cancer.…”
Section: Cancer Stem Cells Play a Key Role In Tumorigenesis And Develmentioning
confidence: 99%